HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP IBU HAMIL DENGAN KEAKTIFAN MENGIKUTI SENAM HAMIL DI WILAYAH PUSKESMAS DUONO - Delista Wodjur, Efan; Sri Purwanti, Anik (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Background: Pregnancy exercise has many benefits for the health of the mother and fetus, such as improving blood circulation, reducing stress, and preparing the body for childbirth. However, the level of participation of pregnant women in pregnancy exercise is often influenced by their level of knowledge and attitudes towards this activity. Objective: This study aims to analyze the relationship between the level of knowledge and attitudes of pregnant women and their activeness in participating in pregnancy exercises in the Duono Community Health Center area. Method: This study used a cross-sectional design with a sample of 16 pregnant women selected using purposive sampling. Data analysis was carried out using the chi-square test to determine the relationship between the variables studied. Results: The results of the study show that the majority of pregnant women who have a good level of knowledge about pregnancy exercise actively participate in pregnancy exercise. The results of the chi-square test show a p value of 0.000 (p < 0.05), which shows that there is a significant relationship between the level of knowledge and attitudes of pregnant women and their activeness in participating in pregnancy exercise. Conclusion: This study concludes that there is a significant relationship between the level of knowledge and attitudes of pregnant women and their activeness in participating in pregnancy exercises in the Duono Community Health Center area. Increasing education and promotion about the benefits of pregnancy exercise is very important to increase the participation of pregnant women in this activity.